The Prevalence of Hepatitis C Virus (HCV) Infection and Genotypes in Patients with Hemophilia and Other Blood Coagulopathies in Mashhad, Iran - Badiei, Zahra; Ahmadi-Ghezaldasht, Sanaz; Sima, Hamid Reza; Habibi, Meysam; Khamooshi, Mohsen; Azimi, Ahmad; Hedayati-Moghaddam, Mohammad Reza (Archives of Medical Laboratory Sciences, 2021)
Background and Aim: Patients with blood coagulopathies treated with multiple transfusions have a high risk to acquire some viral infections such as hepatitis C. This research was aimed to identify hepatitis C virus (HCV) infection prevalence, and the viral genotypes among patients with hemophilia and other inherited coagulopathies in Mashhad, Iran. Methods: Medical records of 760 patients with inherited coagulopathies including hemophilia were reviewed in Sarvar Clinic of Mashhad. Plasma samples were subjected to detect antibodies against HCV (anti-HCV) by enzyme-linked immunosorbent assay. HCV RNA and genotypes were determined by a real-time polymerase chain reaction (PCR) method. Results: Totally 128 individuals (16.8%) including patients with hemophilia (n=116) and individuals with other coagulopathies (n=12) were found to be seropositive for anti-HCV. They comprised 122 men and six women with a mean age of 31.6 ± 10.5 years. The PCR results were available for 118 patients, of whom 86 individuals (72.9%) were found to have detectable HCV RNA in their serum. The most frequent genotypes were 1a and 3a (49.1% and 35.8%, respectively). HCV genotypes were not significantly correlated with the patients’ age (p=0.477) as well as with the serum levels of alanine aminotransferase (p=0.655) and aspartate aminotransferase (p=0.332). Conclusion: The patients with blood coagulation disorders had a greater prevalence of HCV infection in comparison with the general population in our region. The most common subgenotypes of HCV were 1a, and 3a, respectively. These results could assist professionals to choose more efficient approaches for the management of their patients. *Corresponding Author: Mohammad Reza Hedayati-Moghaddam; Email: drhedayati@acecr.ac.ir Please cite this article as: Badiei Z, Ahmadi-Ghezeldasht S, Sima HR, Habibi M, Khamooshi M, Azimi A, Hedayati-Moghaddam MR. The Prevalence of Hepatitis C Virus (HCV) Infection and Genotypes in Patients with Hemophilia and Other Blood Coagulopathies in Mashhad, Iran. Arch Med Lab Sci. 2021;7:1-7 (e9). https://doi.org/10.22037/amls.v7.33968